(untitled) (Delta Medical College Journal, 2013)
Bifidobacteria finds optimal living conditions for growth and overgrowth in the colonized part of the bowel when the chyme is rich in malabsorbed carbohydrate and poor in protein. Such condition is fulfilled with breastfeeding. Though the bifidogenic principle of human milk is attributed to the protein free fraction, the quality and quantity of its protein play an important role in the origination and maintenance of microflora .The low concentration of protein in human milk, the properties of this protein and the presence of specific proteins that inhibit competing microbes in the intestinal microflora are essential components of the bifidogenic principle of human milk. Due to the presence of immunological factors in breast milk like antimicrobial agents, anti-inflammatory agents, and immunomodulatory agents, human milk plays vital protective and defensive role when the infants immune apparatus is immature. It also contributes early childhood growth and development when the infant is absolutely dependent on his/her caregivers for provision of nutrition. DOI: http://dx.doi.org/10.3329/dmcj.v1i1.14972 Delta Med Col J. Jan 2013;1(1):20-24